2016
DOI: 10.1007/s00432-016-2226-0
|View full text |Cite
|
Sign up to set email alerts
|

The crucial role of emilin 1 gene expression during progression of tumor growth

Abstract: Obtained results demonstrated that the suppressive role of emilin 1 is related to the grade of growing breast tumors, and associated with increased hypoxia in the tumor microenvironment followed by elevated unfolding and degradation of tissue proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Our PCR microarray screen suggests that at least 10 ECM-related genes are regulated by PTP4A3. The most provocative is Emilin 1, a member of the Emilin family of proteins, which binds specifically to elastin and is a key component of the ECM in tumor tissue (53,54). Previous studies demonstrated that when Emilin 1 is absent, it alters cell-ECM interactions and enriches the opportunity for migration and invasion, suggesting that Emilin 1 functions as a tumor suppressor (55).…”
Section: Discussionmentioning
confidence: 99%
“…Our PCR microarray screen suggests that at least 10 ECM-related genes are regulated by PTP4A3. The most provocative is Emilin 1, a member of the Emilin family of proteins, which binds specifically to elastin and is a key component of the ECM in tumor tissue (53,54). Previous studies demonstrated that when Emilin 1 is absent, it alters cell-ECM interactions and enriches the opportunity for migration and invasion, suggesting that Emilin 1 functions as a tumor suppressor (55).…”
Section: Discussionmentioning
confidence: 99%
“…EMILIN/Multimerins are a unique family of glycoproteins present in the extracellular matrix (Colombatti et al, 2012). Previous research demonstrated the role of EMILIN/ Multimerins in regulating tumor growth progression (Andreuzzi et al, 2018;Rabajdova et al, 2016) including the association of EMILIN3 in LGG survival rates (Zeng et al, 2018). LGG is a chronic disease characterized by tumor migration, infiltration of the brain's connectome and recurrence after conventional treatment (Delgado-Lopez et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The recently defined elastin microfibrillar interface protein (EMILIN) and Multimerin family is characterized by a C-terminal gC1q globular domain, containing five members: EMILIN1, EMILIN2, EMILIN3, MMRN1 and MMRN2 (Colombatti et al, 2012;Schiavinato et al, 2012). These members have exerted a diverse range of function in the previous study (Capuano et al, 2019;Rabajdova et al, 2016;Schiavinato et al, 2016), which can affect cell growth, wound healing, angiogenesis, lymphangiogenesis and tumor microenvironment, etc. Notably, previous research has reported that high expression of EMILIN3 was confirmed to predict poor survival in LGG (Zeng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These members have exerted a diverse range of function in the previous study (Capuano et al 2019;Rabajdova et al 2016;Schiavinato et al 2016), which can affect cell growth, wound healing, angiogenesis, lymphangiogenesis and tumor microenvironment, etc. Notably, previous research has reported that high expression of EMILIN3 was confirmed to predict poor survival in…”
Section: Introductionmentioning
confidence: 99%